Pressure sores among elderly [Yaşlilarda basi yaralari] - (:unkn) unknown (My University, 2004)
Pressure sores in the elderly. are well-recognized problems, with a multifactorial The elderly with restricted mobility, malnutrition, incontinence, and chronic disease(s) are particularly vulnerable to pressure sore development. Pressure sores can lead to devastating complications and place demands on an already stressed healthcare system. Preventative strategies within the community care setting should concentrate on identifying elderly at risk, mobilization, use of pressure-relieving devices, and additional nutritional support. A multidisciplinary team approach is the most appropriate way to improve prevention and management in this vital area because of complex nature of pressure sore development.